Intra-articular pressure measurement of the first metatarsophalangeal joint of the foot - Castellini, Jorge Luis (Journal of the Foot & Ankle, 2022)
Objective: To measure the metatarsophalangeal (MTP) intra-articular pressure of the first ray before surgical intervention for hallux valgus (HV), recurrent HV, and hallux rigidus (HR). Methods: This is a cross-sectional study including a consecutive sample of patients obtained from 1/1/2009 and 8/30/2015 in a center in Argentina. Measurements were made with a Stryker® pressure gauge, and results were expressed in mmHg. Descriptive and comparative statistics (Mann-Whitney test) were performed. Results: A total of 166 feet were included, 120 cases with HV, 20 with HR, and 26 with recurrent HV; the sample consisted of men and women aged 15 to 90 years. The greater HV deformity, the higher intra-articular pressure at rest and during maximal dorsiflexion and maximal plantar flexion. Conversely, an inverse situation is observed in HR: the greater the deformity, the lower intra-articular pressure. Median resting intra-articular pressure of the first MTP joint of the foot was 3 mmHg in mild HV, compared to 23 mmHg in early-stage HR (p=0.001). Conclusions: The measurement of intra-articular pressure could be a useful tool to differentiate early stages of joint diseases of the first ray of the foot. Level of Evidence II; Prognostic Studies; Retrospective Study.